(3HOGjI GdgOGjIs - (3GdYGedj, GdMQ, eMeO Hf GdMSf Hf Ydj, J (B1104 (3g`s ((3Ydj Hf YHO GdQShd GdNjbGfjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B...(3ajbhd GdabjQ Edi Gddg(B...(3Efj bO GdJeS efj LeGYI ef GdENhGf GdeDefjf GdWGdHjf ddMb Gdjbjf Cf CLeY dge (B...s
(3BNQgG (B:s
...(3jchf GdeLehY KdGKI BdGa EdG SHYI YTQ JbQjHG(B...(3aj HYVgG JOGNd aj HYV hJcQQ(B...s
(3JHUQI GdYfhGf (B:s
(3HOGjI GdgOGjI(B((3NGJeI(B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B90s
(3GdPQjYI(B:(3L(B3(3,U(B55(3,Qbe(B165s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis